What are the Causes of High Crude Oil Price? Causality Investigation - Obadi, Saleh Mothana; Othmanová, Sona; Abdová, Mariam (International Journal of Energy Economics and Policy, 2013)
This paper examines the development of oil prices and identifies the main causes of their development in the last three decades. Of course there are many factors influencing the oil prices, predictable market factors (such as demand and supply) and unpredictable factors (such as political and social turmoil). Therefore, this paper will empirically try to identifying the main causes of movement of the oil prices. This paper also has an ambition to test relation between crude oil and natural gas prices, as substitutes, and the role of decline of natural gas prices in stabilization or destabilization the crude oil market. We have had used in this paper qualitative and quantitative methods such as regression model, Granger causality and structural models. The main findings we have gotten are that the US dollar exchange rate has a significant role in the development of oil prices. We think that the decline in natural gas (as a substitute) prices in the last two years has a slightly impact on stabilization of the oil prices. Keywords: Crude oil prices; natural gas prices; US dollar exchange rate; granger causality; structural model JEL Classifications: C32; Q41; Q43